MiR-129-5p Suppresses Cell Proliferation of Human Osteosarcoma Cancer by Down-Regulating LncRNA Lnc712 - Yu, Yifan (Cancer Manag Res, 2021)
INTRODUCTION: Lnc712 has been characterized as an oncogenic lncRNA in breast cancer. This study aimed to investigate the role of Lnc712 in osteosarcoma (OS). METHODS: OS and paired non-tumor tissues were collected from 58 OS patients. Expression of Lnc712 and miR-129-5p in paired tissue samples was determined by RT-qPCR. Lnc712 and miR-129-5p expression was achieved in OS cells to study the interaction between them. Cell proliferation was analyzed by CCK-8 assay. RESULTS: Lnc712 was upregulated in OS and was inversely correlated with miR-129-5p. In OS cells, Lnc712 overexpression failed to significantly affect miR-129-5p, while miR-129-5p overexpression led to downregulated Lnc712. Cell proliferation showed that Lnc712 overexpression resulted in increased cell proliferation rate. MiR-129-5p overexpression played an opposite role and reversed the effect of Lnc712 overexpression. DISCUSSION: MiR-129-5p may suppress cell proliferation of OS by down-regulating Lnc712.